Treatment of ankylosing spondylitis during pregnancy - O. A. Krichevskaya; T. V. Dubinina; E. V. Ilinykh; S. I. Glukhova; A. B. Demina (Научно-практическая ревматология)
Aims of the trial – to study the frequency of drug use in pregnant women with ankylosing spondylitis (AS), to determine the effect of discontinuation of drugs of various groups, as well as the dose of non-steroidal anti-inflammatory drugs (NSAIDs) used, on AS activity during gestation.Material and methods. 50 pregnancies in 49 patients with AS that met the modified New York criteria of 1984. The average age of the patients was 31.7±4.9 years, the duration of the disease was 134.4±85.8 months. The visits were conducted at 10–11, 20–21 and 31–32 weeks of gestation. The BASDAI in the month of conception and in the I, II and III trimesters of pregnancy was: 1.4 [0.6; 3.3], 2.3 [1.2; 4.4], 2.8 [1.4; 4.2] and 2.2 [1.6; 4.0], respectively. The total dose of NSAIDs was determined by the NSAID intake index (Dougados M., 2011).Results and discussion. NSAIDs. After inclusion in the study, the drug of choice was ibuprofen, which was canceled for all women not later than on 32 week of gestation. At the time of conception and in the first, second and third trim. NSAIDs were taken by 23 (46%), 20 (40%), 30 (60%) and 21 (43.8%) women, respectively. NSAIDs intake index in I trimester (5.8 [2.9; 11.8]) was lower than before pregnancy (28.6 [16.7; 50]) and in II (15.5 [4.7; 30.9]) and III trimesters (24.4 [9.5; 50]) (p<0.05). No relationship between the index of ibuprofen intake, as well as the fact of withdrawal of NSAIDs and AS activity throughout gestation was found. Sulfasalazine (SS) in correspondence with arthritis was taken 3 months before conception by 11 (22%) women, during pregnancy – by 6 (12%) women at a dose of 1.25±0.25 g. Withdrawal of SS was not associated with recurrence of arthritis. Glucocorticoids (GC) at a dose of 7.5±2.5 mg 3 months before pregnancy and in the I, II and III trimesters of pregnancy were taken by 1 (2%), 4 (8%), 8 (16%) and 10 (20.8%) women, of whom 1 patient had arthritis and 1 had inflammatory bowel disease. The rest of the patients received GC due to high AS activity due to axial manifestations and the unavailability of TNFα inhibitors. Against the background of taking GC, the AS activity did not decrease: BASDAI in the II and III trimesters was 5.5±0.6 and 5.8±1.3 (p>0.05). TNFα inhibitors: 3 months before pregnancy and in the trim. of pregnancy were taken by 11 (22%), 7 (14%), 6 (12%) and 2 (4.2%) patients. In those who canceled therapy (both independently and on the recommendation of a rheumatologist) on the eve of pregnancy, an increase in AS activity was noted; BASDAI in the month of conception and in I, II, III trimesters was: 2.7 [0.8; 3.5], 5.1 [3.1; 5.9], 5.5 [5; 6] and 6.7 [5.3; 7.3] (p<0.05) compared to the month of conception. Cancellation of TNF-α in the month of conception was a risk factor for high AS activity (BASDAI>4) in the II trimester (OR=30.4; 95% CI: 1.5–612.3; p=0.03) and in the III trimester (OR=32.7; 95% CI: 1.6–662.2; p=0.02).Conclusion. NSAIDs and GC in low doses do not reduce the activity of AS. Withdrawal of TNF-α inhibitors on the eve of pregnancy is a predictor of high AS activity. It is necessary to increase the knowledge of rheumatologists and patients about the therapeutic possibilities during pregnancy to avoid unjustified drug withdrawal.